Fosfato decantado e calagem no perfilhamento e produção de massa seca do capim-marandu - Leal, Fábio Tiraboschi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The decanted phosphate (DF), by-product of wastewater treatment of phosphoric acid production (H3PO4), is considered an environmental liability and resulting economic obligations to the phosphate fertilizer manufacturers. In this sense, this experiment was conducted in a greenhouse using pots filled with samples of a sandy clay loam Typic Haplustox with main objective to evaluate the effects of DF at tillering and shoot dry matter production of marandu grass (Brachiaria brizantha cv. Marandu) during three consecutive growths in the presence and absence of lime. The experiment was conducted in a completely randomized experimental design with three replications, according to a factorial 6 x 2 x 2 [six rates of P; two sources of P; presence (P/L) and absence of lime (A/L)]. The rates of P were 0, 30, 60, 90, 120 and 150 mg kg-1 of P. The sources of P were the DF and triple superphosphate (TS) (reference source). Lime was applied to the soil in an amount calculated to raise the soil base saturation to 60%. It was found that the phosphate fertilization caused a significant increase in tillers number and shoot dry matter of marandu grass, and the DF did not differ significantly from the TS in the absence of lime, but was significantly lower in the presence of this correction. P supply to the soil by FD was favored by soil acidity which was increased in the course of the experiment The critical levels of P in soil and the marandu grass shoot were 15 mg dm-3 and 1.2 g kg-1, respectively

O fosfato decantado (FD), subproduto resultante do tratamento de efluentes da produção de ácido fosfórico (H3PO4), é considerado um passivo ambiental podendo acarretar obrigações econômicas aos fabricantes de fertilizantes fosfatados. Nesse sentido, conduziu-se esse experimento em casa de vegetação utilizando-se vasos preenchidos com amostras de um Latossolo Vermelho distrófico textura média (LVd) com objetivo principal de avaliar os efeitos do FD no perfilhamento e na produção de massa seca da parte aérea do capim-marandu (Brachiaria brizantha cv. Marandu) por três crescimentos consecutivos, na presença e ausência de calcário. O experimento foi conduzido em delineamento inteiramente casualizado com três repetições, obedecendo a um esquema fatorial 6 x 2 x 2 [seis doses de P; duas fontes de P; presença (C/C) e ausência de calcário (S/C)]. As doses de P foram 0, 30, 60, 90, 120 e 150 mg kg-1 de P. As fontes de P foram o FD e o superfosfato triplo (ST) (fonte de referência). O calcário foi aplicado ao solo em quantidade calculada a fim de elevar a saturação por bases do solo a 60%. Verificou-se que a adubação fosfatada promoveu incrementos significativos na produção de perfilhos e de massa seca da parte aérea do capim-marandu, sendo que o FD não diferiu significativamente do ST na ausência de calcário, porém foi significativamente inferior na presença desse corretivo. O fornecimento de P ao solo pelo FD foi favorecida pela acidez do solo que foi aumentada com o decorrer do experimento. Os níveis críticos de P no solo e na parte aérea do capim-marandu foram 15 mg dm-3 e 1,2 g kg-1, respectivamente
Keywords: Gramínea; Fosfatos; Ion hidrogenio - Concentração; Plantas forrageiras; Calagem dos solos; Grasses